The theology of the Gospel of John - Myers, Alicia D. (New New Testament theology, 2025)
"Placing her study in the context of past and current approaches to John's theology, Alicia Myers explores theological themes with an eye toward the rhetorical categories and aims of the Gospel. Myers argues that John reframes other Gospel traditions and provided important fodder for early Christians debates"--